Answer:
See below
Step-by-step explanation:
13*1 = 13
13*2 = 26
13*3 = 39
13*4 = 52
13*5 = 65
13*6 = 78
13*7 = 91
13*8 = 104
13*9 = 117
13*10 = 130
Just a shot in the dark: 9*30 and 9*8?
Answer:
Blue
Step-by-step explanation:
Hope this helps you out
Exponent is the expression in where you convert product factor expression into a shorter expression. So really you use it to make the question simpler and shorter(easier to understand).
Step-by-step explanation:
<u>Given</u>
- f(x) = 4x³ + 3x² - 2x - 1
<u>Divide it by the following:</u>
<u>(a) 2x + 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 2x²) + (x² + 1/2x) - (5/2x + 5/4) + 1/4 =
- 2x²(2x+1) + 1/2x(2x + 1) - 5/4(2x + 1) + 1/4 =
- (2x + 1)(2x² + 1/2x - 5/4) + 1/4
Quotient = 2x² + 1/2x - 5/4
Remainder = 1/4
<u>(b) 2x - 3</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - 6x²) + (9x² - 13.5x) + (11.5x - 17.25) + 16.25 =
- (2x -3)(2x² + 4.5x + 5.75) + 16.25
Quotient = 2x² + 4.5x + 5.75
Remainder = 16.25
<u>(c) 4x - 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - x²) + (4x² - x) - (2x - 1/2) - 3/2 =
- (4x - 1)(x² + x - 1/2) - 3/2
Quotient = x² + x - 1/2
Remainder = - 3/2
<u>(d) x + 2</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 8x²) - (5x² + 10x) + (8x + 16) - 17 =
- (x + 2)(4x² - 5x + 8) - 17
Quotient = 4x² - 5x + 8
Remainder = - 17